Growth and nutrition of Corymbia citriodora seedlings using doses of liquid swine waste - Coelho, João Antônio da Silva; Vieira, Cristiane Ramos; Weber, Oscarlina Lúcia dos Santos (Comunicata Scientiae, 2018)
The experiment was installed in a greenhouse with the aimed to verify the influence of liquid swine waste in the development and nutrition of Corymbia citriodora seedlings. The swine waste was mixed with a commercial substrate in order to analyze the effects of five doses, in a randomized block design, considering the N requirement of the species, which were T1 – 0%; T2 – 50%; T3 – 100%; T4 – 150% and; T5 – 200% and one treatment with mineral fertilization for comparison. The Corymbia citriodora seeds were germinated in plastic tubes with a commercial substrate plus swine waste. As the seedlings reached about five centimeters the thinning was performed, and when the plants reached 15 cm in length the growth analysis was started. At the end of the experiment the seedlings were measured, weighed and milled for macro and micronutrients determination. The best doses of liquid swine waste were 150% and 200% which showed the highest growth average values of the Corymbia citriodora seedlings, to the detriment of the nutritional and physical improvement of the substrate.